2004
DOI: 10.1002/cne.20189
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of an FMRFamide‐related neuropeptide gene family in Caenorhabditis elegans

Abstract: FMRFamide (Phe-Met-Arg-Phe-NH2) and related peptides (FaRPs) have been found throughout the animal kingdom, where they are involved in many behaviors. We previously identified 22 genes comprising the flp gene family that encodes FaRPs in Caenorhabditis elegans; in this paper we report the identification of another flp gene, flp-23. As a first step toward determining their functional roles in C. elegans, we examined the cell-specific expression pattern of the flp gene family. Of the 19 flp genes examined, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
361
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(381 citation statements)
references
References 84 publications
18
361
0
2
Order By: Relevance
“…In both of these reporter backgrounds, tbx-2(gm111) and tbx-2(ok529) arrested animals had sides with missing cells (Figures 2C9 and 5A) suggesting that the mutation specifically affected PHB. Consistent with this interpretation, the PHA marker ynIs45 (flp-15TGFP) revealed that the tbx-2 mutants were not missing PHAs Kim and Li 2004) (data not shown). Figure 2.-HSN and PHB phenotypes in tbx-2 and tbx-2 gm345 hermaphrodites.…”
Section: Resultssupporting
confidence: 65%
“…In both of these reporter backgrounds, tbx-2(gm111) and tbx-2(ok529) arrested animals had sides with missing cells (Figures 2C9 and 5A) suggesting that the mutation specifically affected PHB. Consistent with this interpretation, the PHA marker ynIs45 (flp-15TGFP) revealed that the tbx-2 mutants were not missing PHAs Kim and Li 2004) (data not shown). Figure 2.-HSN and PHB phenotypes in tbx-2 and tbx-2 gm345 hermaphrodites.…”
Section: Resultssupporting
confidence: 65%
“…FMRFamide-like neuropeptides constitute a major family of C. elegans neuropeptides (Li et al, 1999;Kim and Li, 2004 The relationship between peptidergic and classical neurotransmitter signaling is an interesting topic. In the mammalian brain, the neuropeptide orexin A contributes to learning and addiction via modulation of glutamatergic excitability in dopaminergic neurons (Borgland et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The C. elegans genome contains at least 30 FMRFamide-like neuropeptide ( flp) genes that are predicted to encode over 70 biologically active FMRF-amide like neuropeptides (FLPs) (Li, 2005) (S. Husson and L. Schoofs, personal communication). At least 50% of C. elegans neurons express one or more flp genes (Kim and Li, 2004), indicating their potential roles in the nervous system. We explored flp gene function in regulating C. elegans male sexual behaviors and found that peptidergic signaling modulates the turning step.…”
Section: Introductionmentioning
confidence: 99%
“…LGII: ida-1::gfp(inIs179) (Zahn et al, 2004); LGIII: lin-39fosmid::gfp(wgIs18) (Zhong et al, 2010;Sarov et al, 2012), cat-1::GFP(otIs221) (Flames and Hobert, 2009); LGIV: tph-1::gfp(zdIs13) (Clark and Chiu, 2003), flp-22::gfp(ynIs50) (Kim and Li, 2004); LGV: tph-1::mCherry(cccIs1), tph-1::cfp(bxIs16) (Yang et al, 2007), bas-1::GFP(otIs226) (Flames and Hobert, 2009); LG unknown: flp-21:: gfp(ynIs80), lin-11fosmid::gfp(wgIs62) (Zhong et al, 2010;Sarov et al, 2012), cat-4::gfp(otIs225).…”
Section: Integrated Transgenesmentioning
confidence: 99%